Development of Pop Up Book Media in IPAS Learning on Cultural Wealth Material for Grade IV Elementary School - Fitrianingrum, Dyah Ayu; Rahmawati, Intan; Saputro, Bagus Ardi (FKIP - Universitas Riau, 2025)
This study aims to develop pop-up books as learning media for teaching cultural heritage material in IPAS to fourth-grade elementary students. The research was motivated by low student interest in learning and the limited availability of concrete media, which often causes boredom in class. The study employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with data collected through interviews, observations, questionnaires, and documentation. Validation results showed that the developed pop-up book met feasibility standards. Subject matter expert validation reached an average of 95.5% (very feasible), while media expert validation after revision obtained 82.5% (very feasible). Teacher response was 96% and student response was 85%, both categorized as very good, with an overall average of 90.5%. Furthermore, evaluation tests involving 20 students demonstrated a high level of understanding of cultural heritage content, with most indicators scoring above 90% in correct answers. These findings indicate that the pop-up book is effective and practical, as it not only improves motivation and engagement but also supports deeper comprehension of IPAS material. Therefore, the developed media is considered appropriate for elementary school learning, particularly in enhancing students’ critical and conceptual understanding of cultural diversity.